Current practice of Latin American centers in the treatment of peritoneal diseases with cytoreductive surgery with HIPEC. Issue 11 (November 2018) - ,; Quadros, C.A.; Laporte, G.A.; Huguenin, J.F.L.; Barreto, E.J.S.S.; Barros, A.V.; Oliveira, A.F.; Carvalho, A.L.L.; Petruzziello, A.; Paula, A.C.; Urbano-Ruiz, A.; Santos, C.C.; et al.
Abstract: Introduction: A combination therapy of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) has been proposed as a treatment option in patients with peritoneal metastasis of colorectal, ovarian, gastric cancers and sarcomas and as a current standard treatment for pseudomyxoma peritonei and peritoneal mesothelioma. There is a need to standardize its indication, drugs selection along with their concentrations and ways to deliver peritoneal chemotherapy solutions for best outcomes. Aim of the study: To investigate the current practice of Latin American (LA) Centers in which peritoneal diseases (PD) are treated. Patient and Methods: All centers from Latin American Registry of Peritoneal Diseases (LARPD) were invited to participate in a two rounds online survey, to describe their current practice in all indications of CRS with HIPEC for PD. Results: 76 out of 84 LARPD's centers answered the survey, with a response rate of 90, 5%. The results represent the current practice of 248 surgeons that are members of LARPD's centers, in 8 LA countries, that at the time of the study had treated 2682 patients with CRS with HIPEC. All current practice aspects including indications, contra-indications, patient selection, methods of peritoneal chemotherapy delivery and treatment protocols are described in this manuscript. Conclusions: This survey is the first LA effort to publish current practice indications and treatment protocols of PD. Achieving consensus of best therapeutic options is essential to provide the best possible outcomes for patients with PD who could benefit from CRS with HIPEC therefore aiming at standardization of the procedure.